Prevalence of dyslipidemia and predictive value of anthropometric indicators among children and adolescents in the Tibetan Plateau - Nie, Ming-jian; Sun, Rui-zhe; Fan, Chao-qun; Fei, Xi; Li, Hong-juan (Frontiers in Nutrition, 2025)
Background/ObjectivesDyslipidemia during adolescence has been associated with in-creased risk of cardiovascular disease throughout life; however, its prevalence and anthropometric predictors remain understudied in high-altitude populations. This study aimed to investigate the prevalence of dyslipidemia among children and adolescents in the Tibetan Plateau and evaluate the predictive capability of 15 anthropometric indices [mid-upper arm circumference (MUAC), subscapular skinfold thickness (SST), body mass index (BMI), relative fat mass (RFM), mid-upper arm-to-height ratio (MaHtR), etc.] for dyslipidemia in this population.MethodsA total of 367 Tibetan and Han Chinese students aged 8–17 years were recruited from six schools in Chengguan District, Lhasa (altitude 3,650 m). Anthropometric measurements and lipid profiles were assessed. Dyslipidemia was primarily diagnosed according to the Expert Consensus on Prevention and Treatment of Dyslipidemia in Chinese Children and Adolescents. Receiver Operating Characteristic (ROC) analysis was employed to examine the predictive ability of anthropometric indices for dyslipidemia.ResultsOne in four students (24.25%) had dyslipidemia, with low high-density lipoprotein cholesterol (HDL-C) being found as the predominant phenotype (17.98%). Han Chinese students exhibited higher dyslipidemia prevalence compared to their Tibetan counterparts (13.62 vs. 10.63%), with higher rates observed among females than males (14.17 vs. 10.08%). Junior high school students demonstrated the highest prevalence among the three grade groups (11.99 vs. 6.54 vs. 5.72%). Most anthropometric indices showed the area under the ROC (AUC) values below 0.6, with only MUAC, SST, BMI, RFM, and MaHtR demonstrating significant diagnostic accuracy. Their highest AUC values in subgroups reached only 0.651 and were not consistently applicable across all subpopulations.ConclusionsChildren and adolescents in the Tibetan Plateau demonstrate a high prevalence of dyslipidemia, particularly among Han Chinese students, girls and junior high school students. Low HDL-C emerged as the primary dyslipidemia phenotype. Most anthropometric indices demonstrated limited diagnostic capability for dyslipidemia among plateau children and adolescents, with only BMI, SST, MUAC, MaHtR, and RFM showing weak yet promising diagnostic value.